Is HUGO still the BOSS? Investigating the reciprocal effects of brand extensions on brand personality of luxury brands. Issue 4 (November 2021) - Phau, Ian; Matthiesen, Insa-Mascha; Shimul, Anwar Sadat
This research aims to empirically investigate positive and negative reciprocal effects of extensions on brand personality by varying levels of congruency and typicality, while controlling for the effects of motivation processing. A 2 (incongruent, congruent) × 2 (high typicality, low typicality) × 2 (high motivation, low motivation) research design was employed using two extension categories, namely watches and kidswear of the HUGO BOSS brand. The findings revealed brand personality dilution effects only. Specifically, brand personality dilution occurred in response to incongruent and congruent information. Further, contrary to schema theory, brand personality evaluations neither strictly followed the bookkeeping model in high-motivation conditions nor the subtyping model in low-motivation conditions in response to in-congruent information.